Effects of Production Method and Repeated Freeze Thaw Cycles on Cytokine Concentrations and Microbial Contamination in Equine Autologous Conditioned Serum - Hale, Josephine; Hughes, Kristopher; Hall, Sarah; Labens, Raphael (Frontiers in Veterinary Science, 2021)
Autologous conditioned serum (ACS) is a common intra-articular treatment for osteoarthritis in horses. The objective of this study was to investigate the influence of ACS preparation method on product contamination and concentrations of relevant cytokines and the influence of multiple freeze/thaw cycles. Blood was obtained from 10 healthy Thoroughbred horses and processed in parallel using a commercial and a non-commercial method to obtain ACS. Fluorescent microsphere immunoassay (FMIA) analysis was performed to quantify Interleukin 1 receptor antagonist (IL-1Ra), Interleukin-10 (IL-10), Interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α) concentrations in ACS obtained by both production methods. Effect of 3, 4 and 5 freeze/thaw cycles on concentrations of IL-1Ra, IL-10, IL-1β and TNF-α were assessed against baseline samples (2 cycles) in commercial ACS products. Standard aerobic and anaerobic culture methods were applied to both ACS products. Mixed effect one-way analyses of variance (ANOVA) were used to compare the two ACS production method for each cytokine. Repeated measures, mixed effect ANOVA were used to assess the effect of freeze/thaw on cytokine concentrations. Significance was set at P < 0.05. There was no difference in cytokine concentration between production methods (IL-1Ra P = 0.067, IL-1β P = 0.752, IL-10 P = 0.211 and TNF-α P = 0.25). Microbial growth was only observed in two samples obtained using the commercial production method. When compared to baseline, IL-1Ra concentration was decreased following the 5th freeze/thaw cycle (P < 0.001). These results suggest that the concentration of important cytokines are not influenced by ACS production method. When storing ACS samples for future use, freeze/thaw cycles associated with standard clinical practice are unlikely to influence cytokine concentrations. However, the lack of outcome measures associated with 1 or 2 freeze/thaw cycles represents a limitation of this study. Keywords: ACS, Osteoarthritis, IRAP, Horse, Thermal Stability